2014
DOI: 10.4081/rt.2014.5529
|View full text |Cite
|
Sign up to set email alerts
|

Response to Targeted Therapy in Urachal Adenocarcinoma

Abstract: We report the case of a young woman diagnosed with metastatic urachal carcinoma. A multimodal approach was used for the management of this patient. Due to disease progression despite surgery and two different chemotherapy regimens (neoadjuvant capecitabine + irinotecan + oxaliplatin and docetaxel + cisplatin after surgery), treatment with sunitinib was eventually started. Treatment with sunitinib resulted in stable disease and improvement of symptoms. Sunitinib was discontinued due to the occurrence of metrorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…The immunohistochemical markers most often employed in the work up of adenocarcinomas of different sites usually include Cytokeratin 20 (CK20) and CK7. In our analysis of a total of 116 urachal adenocarcinomas, only 4 cases were negative for CK20—an overall positive rate of 97% [ 1 , 17 , 23 , 26 , 27 , 31 , 36 , 48 , 56 , 60 , 62 , 67 , 74 , 77 , 86 , 95 , 99 , 124 126 , 128 , 148 , 156 , 163 , 164 , 216 , 217 , 220 , 240 , 245 , 251 , 327 ]. Considering the robust CK20 expression in adenocarcinomas of sites of differential diagnostic interest, CK20 has no significant value in this setting.…”
Section: Biomarkers In Urachal Cancer: Immunohistochemistrymentioning
confidence: 83%
See 2 more Smart Citations
“…The immunohistochemical markers most often employed in the work up of adenocarcinomas of different sites usually include Cytokeratin 20 (CK20) and CK7. In our analysis of a total of 116 urachal adenocarcinomas, only 4 cases were negative for CK20—an overall positive rate of 97% [ 1 , 17 , 23 , 26 , 27 , 31 , 36 , 48 , 56 , 60 , 62 , 67 , 74 , 77 , 86 , 95 , 99 , 124 126 , 128 , 148 , 156 , 163 , 164 , 216 , 217 , 220 , 240 , 245 , 251 , 327 ]. Considering the robust CK20 expression in adenocarcinomas of sites of differential diagnostic interest, CK20 has no significant value in this setting.…”
Section: Biomarkers In Urachal Cancer: Immunohistochemistrymentioning
confidence: 83%
“…In contrast, expression of CK7 in these tumors is widely variable. In urachal adenocarcinomas, CK7 exhibited a pooled reactivity rate of 51%, compared to considerable lower rates in colorectal cancer (0–38%, Table 2 , Supplementary Table 2 ) [ 1 , 17 , 23 , 26 , 27 , 31 , 36 , 48 , 56 , 60 , 67 , 74 , 77 , 86 , 99 , 124 , 125 , 156 , 163 , 164 , 216 , 217 , 220 , 240 , 251 , 255 , 292 , 327 , 328 ]. However, similar to urachal adenocarcinomas, primary bladder adenocarcinomas constantly exhibited relatively high CK7 reactivity rates (33%–70%), thus limiting the value of CK7 in the discrimination between these two entities [ 23 , 329 ].…”
Section: Biomarkers In Urachal Cancer: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are only few, however, promising data on the efficacy of targeted therapies in UrC. Testa et al [36] reported a necrotic involution of the tumor and a significant improvement of abdominal pain in a patient with metastatic UrC who was treated with secondline multikinase inhibitor (sunitinib) following failure of platinum-containing combination chemotherapy.…”
Section: Therapymentioning
confidence: 97%
“…To date there are only few, however promising data on the efficacy of targeted therapies in UrC. Testa et al reported a necrotic involution of the tumor and a significant improvement of abdominal pain in a UrC patient who was treated with second-line multikinase inhibitor (Sunitinib) [6], while Goss et al observed a size regression of a UrC as a response to EGFR-inhibitor therapy with gefitinib (Iressa) [7]. Finally, a recent study reported a patient with lung metastatic UrC who was effectively treated with a monoclonal EGFR-inhibitor (cetuximab) for eight months [8].…”
Section: Introductionmentioning
confidence: 99%